2017
DOI: 10.1007/s00265-017-2356-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to predators reduces collective foraging aggressiveness and eliminates its relationship with colony personality composition

Abstract: Predation is a ubiquitous threat that often plays a central role in determining community dynamics. Predators can impact prey species by directly consuming them, or indirectly causing prey to modify their behavior. Direct consumption has classically been the focus of research on predator-prey interactions, but substantial evidence now demonstrates that the indirect effects of predators on prey populations are at least as strong as, if not stronger than, direct consumption. Social animals, particularly those th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…This suggests that behavioral inconsistency (IIV) can predict outcomes of predator-prey interactions that average behavior (personality) cannot. This suggests that numerous studies probing the role of personality in spider feeding behavior 38 – 40 may not have considered all relevant intraspecific behavioral variation. Notably, neither average activity level nor activity IIV predicted the number of prey that spiders consumed (Table 1 ), meaning that variation in activity level both within and across individuals is seemingly unrelated to prey capture success.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that behavioral inconsistency (IIV) can predict outcomes of predator-prey interactions that average behavior (personality) cannot. This suggests that numerous studies probing the role of personality in spider feeding behavior 38 – 40 may not have considered all relevant intraspecific behavioral variation. Notably, neither average activity level nor activity IIV predicted the number of prey that spiders consumed (Table 1 ), meaning that variation in activity level both within and across individuals is seemingly unrelated to prey capture success.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on collective behaviour have focused on a single biological context [ 30 ], and experimental tests of how the environmental context may result in group-level changes in behaviour have been limited (e.g. [ 35 , 36 ]). Whether animal groups exhibit repeatable behavioural differences across ecological contexts thus remains an open question.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the fission–fusion dynamics of groups of bats ( Kerth 2010 ) and birds ( Aplin et al 2013 ) is influenced by the personality of each individual; the aggregation dynamics of Periplaneta americana (Linnaeus, 1758) (Blattodea: Blattidae) is influenced by individual and group personalities ( Planas-Sitjà et al 2015 ); and individual personality in stickleback fish strongly affected the group’s structure, movement dynamics, and foraging behavior ( Jolles et al 2017 ). Regarding fleeing behavior, different studies have found the existence of behavioral syndromes ( Carter et al 2010 , Niemelä et al 2012 , Seltmann et al 2012 , Cooper Jr and Blumstein 2015 ) and that some events, like an increase of risk or stress, might break apart individual personalities ( Niemelä et al 2012 , Cote et al 2013 , Wright et al 2017 ).…”
mentioning
confidence: 99%